CONTRIBUIÇÕES DAS REDES SOCIAIS LIVRESCAS PARA A SOCIABILIDADE LITERÁRIA - GONÇALVES, MARINA (2022)
The delimitation of the object of study of this dissertation focuses on the contributions of the social network Skoob for literary education, in a formal teaching environment, specifically a third grade high school class, with nine research subjects. The choice of this object of study is justified by exploring new ways to promote the formation of readers and to problematize practices rooted in literary reading in formal teaching environments. For this purpose, an empirical participant research was undertaken, with a qualitative approach, in the outsider modality. In the twelve meetings of the intervention, data collection materials such as questionnaires, research diary, observation script, and social network movements of the research subjects were used. After all the volumes of data were gathered, the analysis was undertaken, based on categorizations and cross-referencing of information. The theoretical framework of this research was composed of Bakhtin Circle's dialogic studies, specifically dialogism, represented mainly by Volóchinov (2013, 2018, and 2019) and Bakhtin (2006); for the sociointeractionist discussion, strictly the concept of mediation, Vygotsky (2001) was used; about the Aesthetics of Reception, the emphasis on the reader was brought from Jauss (1994) and Zilberman (1989); for the didactics of literature, the studies on shared reading were based mainly from Colomer (2007); and about the concept of network, the basis was the studies of Recuero (2009). The general objective was to understand the scope of literature shared reading through the social network Skoob, in a formal teaching context. The specific objectives were: to verify the acceptance of the book social network Skoob in a formal teaching context; to examine whether Skoob can be useful to promote shared reading; to describe and understand how literary sociability occurs among readers during the teaching-learning process; and to investigate whether the use of the social network contributes to the promotion of literary reading. The results indicated that the social network Skoob has several features that can be explored by teachers and that shared reading and mediation are fundamental to the successful use of the platform, since they contribute productively to literary sociability. Furthermore, Skoob proved to be efficient in encouraging students to write and exchange reading experiences in a social environment.